EVALUASI MODEL MODIFIKASI KETERAMPILAN DASAR BERMAIN SEPAKBOLA USIA10-17 TAHUN PADA SEKOLAH SEPAK BOLA BINTANG MUDA BANDA ACEH - Irfandi Irfandi (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2019)
Research aims to know the basic skill level of playing the age of 10-17 years at the Football School (SSB) of the young star of Banda Aceh.